MUSCULAR ANATOMY OF THE THORAX AND THORACIC LIMB OF Caiman Crocodilus (LINNAEUS, 1758) (CROCODYLIA: ALLIGATORIDAE) BY MEANS OF DIGITAL DISSECTION AND THREE-DIMENSIONAL MODELS - Romão, Mariluce Ferreira; Santos, André Luiz Quagliatto (Brazilian Journal of Implantology and Health Sciences, 2023)
The Caiman crocodilus , popularly known as alligator , is a species of crocodilian, which has a crest or "forehead" described as "in crescent shape", observed, immediately, dorsal in relation to the eyes, as well as above the dorsal region of the snout, with an ossified crust rostral to the orbicular region. The present study aimed to describe the muscular anatomy of the thorax with emphasis on the thoracoappendicular muscles, and Caiman crocodilus thoracic limb , with the aid of X-Ray (RX), Ultrasonography (US), and detailed manual dissection; identified the thickness of the muscle groups of the thorax and thoracic limb of the Caiman crocodilus , through Ultrasonography, and, at the end, three-dimensional models of the muscular anatomy of the thorax were built, with emphasis on the thoracoappendicular muscles, and the thoracic limb of the Caiman crocodilus , with finalization in three-dimensional PDF. Anatomical descriptions have greatly favored interventions in wild animals, as well as the use of imaging tests such as X-ray and US. In addition, 3D schematic models clarify topographical relationships and highlight muscle depth, for example. In this way, it is possible to identify anatomical differences and intervene in case of diagnoses and prognoses, such as in US, even in real time.